Randomized Trial of Self-Selected Music Intervention on Pain and Anxiety in Emergency Department Patients with Musculoskeletal Back Pain - Charlotte E. Goldfine; Jenna M. Wilson; Jenson Kaithamattam; Mohammad Adrian Hasdianda; Kate Mancey; Alexander Rehding; Kristin L. Schreiber; Peter R. Chai; Scott G. Weiner (Western Journal of Emergency Medicine)
Introduction: Acute musculoskeletal back pain is a frequent cause of emergency department (ED) visits, often with suboptimal relief from standard treatments. Recent evidence suggests listening to music may modulate pain and anxiety. In this pilot randomized controlled trial, we evaluated the impact of a brief session of patient-selected music vs noise cancellation on pain severity and anxiety in patients presenting to the ED with back pain. Methods: Patients with acute back pain completed a baseline survey to assess demographics, medication information, and psychosocial factors. The ED patients were randomized to listen to self-selected music or to noise cancellation (control). Patients rated their pain and anxiety (0–10) before and immediately after the intervention. We used analyses of covariance to examine whether post-intervention pain and anxiety differed between the groups, while controlling for baseline trait pain catastrophizing. A mediation analysis was conducted to explore the role of post-intervention anxiety as a mediator of the group difference in post-intervention pain. Results: Forty patients were enrolled with an average age of 47.2 years (range 21 – 81). and 27 patients (68%) were female. At baseline, patients in the music group reported higher pain catastrophizing compared to patients in the noise cancellation group. There were no other group differences in baseline characteristics. Post-intervention, patients in the music group reported significantly lower anxiety (3.0 ± 0.7 vs 5.5 ± 0.7, P = 0.016) and pain severity (6.1 ± 0.4 vs.7.5 ± 0.4, P = 0.037) compared to the noise cancellation group. A mediation analysis showed that post-intervention anxiety partially mediated the association between intervention group (music vs noise cancellation) and post-intervention pain. Conclusion: A brief session of self-selected music resulted in lower pain and anxiety scores than noise cancellation among patients with musculoskeletal back pain in the ED. Patients who listened to music reported lower post-intervention anxiety, which partially contributed to lower post-intervention pain severity.